Differential expression analysis of salt stress related genes TaSRG and TaRUB1 in contrasting wheat genotypes - Ram, Sewa; Rana, Veenti; Nehra, Kiran; Sharma, Indu (Journal of Cereal Research, 2025)
The present investigation was carried to study the differential expression of two salt stress related genes TaSRG and TaRUB1 in wheat genotype Kh 65 (salt tolerant) and HD 2009 (salt sensitive). The study was conducted under controlled conditions in growth chamber (800 Âµmol/M2S: 14h light 200C and 10h dark at 160C) in sandy soil saturated with half strength of Hoagland solution. Salt treatment was given to 7 days old seedlings for three days with final ECe of 12.0. There was 16 fold increase in expression level of TaSRG in in roots of Kh 65 and 2 fold in HD 2009 and in shoot it increased 9 fold in Kh 65 and 4 fold in HD 2009. TaRUB1 expressed 12 fold more in shoot of Kh 65 at 48 hrs of salt treatment and no significant change in HD2009 while it increased 7 fold in roots of Kh 65. Higher expression of both these genes in tolerant genotype indicated their important role in salinity tolerance in wheat.